2020
DOI: 10.1007/s11845-020-02211-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective properties of leptin in patients with excessive body mass

Abstract: Background Adipose tissue is producing adipokines that play different roles in the pathophysiology of cardiovascular disease. Aims The study aimed to assess the role of selected biomarkers in hypertensive patients with overweight and obesity compared with those with normal body-mass index (BMI). Methods A total of 62 patients with BMI < 25 kg/m 2 (median age 54 (46-58) yrs., 57% males) and 51 with BMI ≥ 25 kg/m 2 (median age 53 (48-59) yrs., 37% males) were enrolled. Biochemical parameters, leptin, adiponectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
1
6
0
2
Order By: Relevance
“…The authors underline that the reduction of excessive body weight is particularly beneficial for patients taking antihypertensive drugs. At the same time, the findings of Paduszyńska et al [9] provide evidence that the choice of adequate pharmacotherapy for hypertension enables the control of systolic and diastolic blood pressure, regardless of the BMI value. In this study, we observed that in some patients arterial hypertension was accompanied by other comorbidities.…”
Section: Discussionmentioning
confidence: 97%
“…The authors underline that the reduction of excessive body weight is particularly beneficial for patients taking antihypertensive drugs. At the same time, the findings of Paduszyńska et al [9] provide evidence that the choice of adequate pharmacotherapy for hypertension enables the control of systolic and diastolic blood pressure, regardless of the BMI value. In this study, we observed that in some patients arterial hypertension was accompanied by other comorbidities.…”
Section: Discussionmentioning
confidence: 97%
“…50 Our results have shown the relationship between leptin, PWV, and newly diagnosed hypertension. Gonzalez et al 10 and Paduszyńska et al 11 presented correlations between high levels of serum leptin and hypertension and AS. Our results are also confirmed by the Inter99 study where leptin, but not adiponectin or C reactive protein, may have played a mediating role in overweight-induced hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…4 The current literature indicates that the levels of adipokines are associated with hypertension and blood pressure (BP) control 5 7 and vascular manifestations of the condition. 8 11…”
Section: Introductionmentioning
confidence: 99%
“…Антигипертрофический эффект лептина показан в ряде экспериментальных данных и ассоциирован с нарушением лептиновой сигнализации [43,44]. Серия исследований на людях показывает антигипертрофический эффект лептина, демонстрируя аналогичные результаты, полученные в представленной работе [45][46][47][48]. В популяционном перекрестном исследовании, проведенном M. Pladevall et al на выборке пациентов с избыточной массой тела на доклинической стадии СН после поправки на пол, возраст, САД, HOMA-IR, уровень циркулирующего лептина отрицательно ассоциировался с ММЛЖ/рост 2,7 [45].…”
Section: Comorbid Patientunclassified